2021
DOI: 10.3746/pnf.2021.26.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Mentha cordifolia Leaf Extract Improves Hepatic Glucose and Lipid Metabolism in Obese Mice Fed with High-Fat Diet

Abstract: Mentha cordifolia (MC) is a popular herb used to flavor food in Thailand that exhibits several biological effects. The present study aimed to determine the role of MC in regulating glucose and lipid metabolism in mice fed a high-fat diet (HFD). ICR obese mice were fed an HFD (45 kcal% lard fat) for 12 weeks, with MC (100 and 200 mg/kg/d) treatment from Week 7. After treatment with MC for 6 weeks, mice showed significantly lower rates of hyperglycemia, hyperinsulinemia, hyperleptinemia, and hyperlipidemia, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
3
6
0
Order By: Relevance
“…In agreement with previous studies [36,37], HFD feeding resulted in adipose tissue inflammation, as evidenced by increased CLS formation and expressions of macrophage marker gene F4/80, along with increased inflammatory gene expressions, including NF-κB p65, MCP-1, TNF-α, and iNOS, in the HFD group compared to the LFD group (Figure 2D,E and Figure 4A-D). The ELISA results confirmed an increase in the serum levels of TNF-α in mice fed an HFD (Figure 4F), which is one of the main biomarkers of systemic inflammation; this finding is consistent with a previous study [38]. Nevertheless, our result shows that the 12-week HFD feeding duration is not sufficient to increase serum MCP-1 levels (Figure 4E), indicating that this duration is not long enough to induce increased production of this chemokine.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with previous studies [36,37], HFD feeding resulted in adipose tissue inflammation, as evidenced by increased CLS formation and expressions of macrophage marker gene F4/80, along with increased inflammatory gene expressions, including NF-κB p65, MCP-1, TNF-α, and iNOS, in the HFD group compared to the LFD group (Figure 2D,E and Figure 4A-D). The ELISA results confirmed an increase in the serum levels of TNF-α in mice fed an HFD (Figure 4F), which is one of the main biomarkers of systemic inflammation; this finding is consistent with a previous study [38]. Nevertheless, our result shows that the 12-week HFD feeding duration is not sufficient to increase serum MCP-1 levels (Figure 4E), indicating that this duration is not long enough to induce increased production of this chemokine.…”
Section: Discussionsupporting
confidence: 92%
“…The abnormal lipid metabolism in the liver and adipose tissue results in hepatic steatosis, typically promoting the secretion of lipids, and hence, contributing to high circulating FFA levels, hypertriglyceridemia, and hypercholesterolemia [ 4 , 6 ]. Consistent with previous reports [ 20 , 21 , 26 , 27 , 28 ], our findings showed that HFD-fed animals presented the typical features of hepatic steatosis and hyperlipidemia, including high serum FFA, hypertriglyceridemia, and hypercholesterolemia, associated with the elevated expression of ATGL in adipose tissue, CD36, LXRα, SREBP-1c, SREBP-2, and HMGCR, as well as decreased CPT1A expression in the liver, which were overall reversed by RRBE treatments, especially at the middle and high doses. Interestingly, although a high-dose RRBE treatment did not reduce serum total-C in HFD-fed mice, it significantly attenuated LDL-C and enhanced HDL-C in the serum, as discussed in more detail below.…”
Section: Discussionsupporting
confidence: 94%
“…This study indicates that dyslipidemia, NAFLD, and obesity were successfully induced in our model by feeding the mice with HFD, which may be due to the significant increase in their energy intake. Our results are in accordance with those reported by previous studies [ 20 , 21 , 26 , 27 , 28 , 29 , 30 , 31 ]. Thus, this model is appropriate for examining the precise mechanisms underlying the anti-dyslipidemic and anti-NAFLD activities of RRBE.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Mentha villosa Huds (the synonym of Mentha cordifolia ) is another popular herb typically used both as flavour in Thai food and as herbal tea. It has been shown to improve lipid metabolism and glycemia in obese mice treated with M. villosa leaf extract for six weeks, leading to a reduction in GLU, insulin, leptin, TG levels, and in the inflammatory cytokines IL-6 and TNFα, and an increase in adiponectin level, accompanied with the activation of the AMPK signaling pathway [ 69 ] ( Table 2 ).…”
Section: Lamiaceae: Bioactive Propertiesmentioning
confidence: 99%